Third Five-Year Plan Andhra Pradesh Review of Progress 1961-62 - Planning Commission (Planning Commission, 1961)
The State of Andhra Pradesh extends over an area of 1,06,286 square miles with a population of 35.98 millions according to 1961 census. It ranks 4th in the size of population next to Uttar Pradesh, Bihar and Maharashtra and 5th in area next to Madhya Pradesh, Rajasthan, Maharashtra and Uttar Pradesh amongst the States of India. The density of population of the State is 339 per sq. mile which is less than the All India Average of 373 per square mile.
Bureau of Economic and Statistics, Government of Andhra Pradesh